Pengaruh Media Sosial Dating Apps Bumble terhadap Perilaku Menyimpang pada Remaja di Universitas Medan Area - Hutagaol, Camelia Chairunissa; Auza, Ara (Universitas Medan Area, 2025)
The use of online dating applications such as Bumble is becoming increasingly popular among teenagers and young adults, offering convenience in building social relationships. However, these applications also have the potential to encourage deviant behavior that can impact users' social and psychological well-being. This study aims to analyze the influence of Bumble usage on deviant behavior among teenagers at Universitas Medan Area using a qualitative approach through in-depth interviews. The findings indicate that, besides being used to find romantic partners, Bumble is also utilized for entertainment and expanding social networks. However, several forms of deviant behavior were identified, including identity manipulation, emotional exploitation, and an increased risk of casual relationships. Additionally, excessive reliance on online communication may reduce face-to-face social interaction skills. These findings highlight the importance of digital literacy and stricter policies from app developers to minimize negative impacts. This study contributes to the fields of communication and sociology while providing insights for educators, parents, and app developers in understanding the dynamics of teenage social interactions in the digital era.